THU0303 The early psoriatic arthritis screening questionnaireidentifies patients with psoriatic arthritis amongst treated patients with psoriasis. (12th June 2018) - Nadeau, K.; Briggs, F.; O'Neill, S.; Sumpton, D.; Cains, G.; Woods, J.; Chessman, D.
Abstract : Background: Studies suggest a high prevalence (approximately 15%) of undetected psoriatic arthritis (PsA) amongst patients with psoriasis 1 . A number of screening questionnaires have been designed to allow detection of such patients. This includes the Early Psoriatic Arthritis Screening Questionnaire (EARP) which detects early PsA in untreated patients with psoriasis, with a sensitivity of 85.2% and specificity of 91.6% 2 . Little is known about whether such questionnaires are also able to detect PsA in treated patients with psoriasis. Objectives: To determine the case finding ability of EARP in a tertiary centre cohort of treated psoriasis patients. Methods: All patients attending a tertiary centre psoriasis clinic were invited to complete the EARP. EARP comprises a 10 point patient reported questionnaire regarding symptoms of joint disease. Scores of 3 or more are considered positive. All patients who completed the questionnaire and received a positive score were assessed by a rheumatologist. Diagnosis of PsA was made by clinician impression and CASPAR criteria. Disease activity was assessed using psoriasis area severity index (PASI), 66/68 swollen and tender joint count, SPARCC enthesitis index, CRP and Health associated quality of life disability index (HAQ-DI). The composite disease activity measure DAPSA and the OMERACT definition of minimal disease activity were determined. Results: 133 patients were invited to complete the EARP questionnaire and 119 participated. Fifty patients had a positive result (42%). Of these, 8 were known to have PsA and under rheumatologic care. A further 21 attended for formal rheumatologic assessment. Thirteen of the 21 patients (61.9%) were found to have psoriatic arthritis and were not under the care of a rheumatologist. This represents 10% of the initial 133 patients screened. Ten of those patients were further assessed. The average age was 52.8 and BMI 33.2. Seven patients were male. All 10 were on biologic agents but only 3 on concurrent conventional DMARDs. Average tender joint count was 16, swollen joint count 3.6, SPARCC 6.2 and PASI score 3.42. Only 1 patient was in minimal disease activity. Conclusions: The EARP tool can identify patients with active PsA amongst patients with psoriasis, even those on treatment with biologic agents. Such a tool may be useful in identifying patients who may benefit from rheumatology care. References: [1] Villani AP, Rouzaud M, et al. Prevalence of undiagnosed psoriatic arthritis among psoriasis patients: Systematic review and meta-analysis.J Am Acad Dermatol2015;73(2):242–8. [2] Tinazzi I, Adami S, Zanolin EM, et al. The early psoriatic arthritis screening questionnaire: a simple and fast method for the identification of arthritis in patients with psoriasis. Rheumatology2012;51(11):2058–63. Disclosure of Interest: None declared